2017
DOI: 10.18552/joaw.v7i1.214
|View full text |Cite
|
Sign up to set email alerts
|

Revision Processes in First Language and Foreign Language Writing: Differences and Similarities in the Success of Revision Processes

Abstract: Writing academic texts in one's native language (L1) and -even more -in a foreign language (FL) places high cognitive demands on students. In order to cope with these demands, writers should learn to adapt their writing methods flexibly to their tasks, depending on the language and the genre they are writing in. Crucial aspects here are the methods of revising because the need for linguistic revision will be higher in the FL text than in the L1 text; at the same time, it should not be the main or only focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…There are very few, if any, spelling errors related to crosslinguistic transfer in the texts. This is in line with the results of the study by Odilia Breuer (2017), but not with those of the studies by Andersson (1981) and Zetterholm (2017). All participants in this study were early second language learners of Swedish who usually use Swedish at school and another language at home.…”
Section: Conflicts Of Interestsupporting
confidence: 90%
See 2 more Smart Citations
“…There are very few, if any, spelling errors related to crosslinguistic transfer in the texts. This is in line with the results of the study by Odilia Breuer (2017), but not with those of the studies by Andersson (1981) and Zetterholm (2017). All participants in this study were early second language learners of Swedish who usually use Swedish at school and another language at home.…”
Section: Conflicts Of Interestsupporting
confidence: 90%
“…The researchers concluded that revisions depended more on students' linguistic experience than on their linguistic competence. In a study by Odilia Breuer (2017), German students of English philology wrote texts on different topics in their L1 (German) and their foreign language (English). At a broad level, the same revisions were made in both texts by the students, although analyses at a deep level showed differences related to students' linguistic competence.…”
Section: Writing Processes and Revisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second and third authors and 12 graduate students administered two reading tests to screen for literacy disabilities for a larger project, which were the Pseudoword (Nonword) and Word Reading subtests from the Salzburg Reading and Orthography Test II (Moll & Landerl, 2010). Both tests have high test–retest reliability coefficients across grades (.80 and .97) and correlate highly ( r ≥ .75) with the Salzburg Reading Screening Instrument (Breuer, 2017). Based on the two tests, the current sample had a number of students at risk for reading disabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies have suggested that German L2 learners had lower spelling proficiency than their L1 counterparts had (Festman & Schwieter, 2019). In addition, Breuer (2017) found that adult German L2 students performed significantly poorer than L1 students did in spelling and writing tasks. Bassetti (2017) suggested that the orthographic similarity between L1 and L2 might influence L2 spelling proficiency.…”
Section: Role Of Decoding and Home Language In Individual Spelling Pr...mentioning
confidence: 96%